First record of the Neolicaphrium recens Frenguelli, 1921 (Mammalia, Litopterna) in the Pleistocene of Santiago del Estero Province, Argentina - Gaudioso, Pablo J. (2017)
Fil: Gaudioso, Pablo J.. Universidad Nacional de Tucumán. Facultad de Ciencias Naturales e Instituto Miguel Lillo. Programa de Investigaciones de Biodiversidad Argentina; Argentina